Mortgage Pricing and Monetary Policy - Benetton, Matteo; Gavazza, Alessandro; Surico, Paolo (American Economic Review, 2025)
This paper examines how central bank policies influence mortgage pricing in the United Kingdom. It shows that lenders price discriminate by offering two-part tariffs of interest rates and origination fees, and during unconventional monetary policies like the Funding for Lending Scheme, lenders reduced interest rates while increasing fees. Using a model of mortgage demand and lender competition, we find that central bank policies increased mortgage lending. Additionally, banning origination fees would reduce lending, as fees help lenders capture surplus while allowing them to price discriminate across borrowers with different sensitivities to rates and fees. (JEL E43, E52, E58, G21, G28, R31)